2022
DOI: 10.3390/antibiotics11040436
|View full text |Cite
|
Sign up to set email alerts
|

Linezolid Administration to Critically Ill Patients: Intermittent or Continuous Infusion? A Systematic Literature Search and Review

Abstract: A judicious antibiotic therapy is one of the challenges in the therapy of critically ill patients with sepsis and septic shock. The pathophysiological changes in these patients significantly alter the antibiotic pharmacokinetics (PK) and pharmacodynamics (PD) with important consequences in reaching the therapeutic targets or the risk of side effects. The use of linezolid, an oxazolidinone antibiotic, in intensive care is such an example. The optimization of its therapeutic effects, administration in intermitte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…Linezolid is a last-line drug to treat complicated outcomes from multiclass-resistant Gram-positive bacteria, such as vancomycin-resistant Enterococcus spp. and Staphylococcus aureus exhibiting methicillin resistance [ 5 ]. Among the acquired (mobile) linezolid resistance mechanisms, the optrA gene has been reported as being responsible for the recent emergence in linezolid-resistant enterococci among isolates from human clinical sources [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Linezolid is a last-line drug to treat complicated outcomes from multiclass-resistant Gram-positive bacteria, such as vancomycin-resistant Enterococcus spp. and Staphylococcus aureus exhibiting methicillin resistance [ 5 ]. Among the acquired (mobile) linezolid resistance mechanisms, the optrA gene has been reported as being responsible for the recent emergence in linezolid-resistant enterococci among isolates from human clinical sources [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“… 26 , 28 The pharmacokinetic–pharmacodynamic target was the fAUC24h:MIC ratio of at least 100, which has been shown to predict clinical efficacy for other bacterial infections. 30 In our simulations ( appendix p 3 ), linezolid concentrations reached a fAUC24h:MIC ratio of 128·0, exceeding 100.…”
Section: Methodsmentioning
confidence: 68%
“… 44 We expected this dosage to be effective on the basis of initial pharmacokinetic–pharmacodynamic calculations, with fAUC24:MIC ratios used as predictors of efficacy in other bacteria. 30 However, this approach to dose selection has limitations, because it relies on point estimates and might not account for patient-specific factors such as age, gender, weight, and individual variations in drug metabolism, which can influence linezolid efficacy. Alternative mathematical models, such as Monte Carlo simulations, can more easily consider variability and might offer more accurate predictions of effectiveness in the population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Linezolid, the first clinically available oxazolidinone, is globally used in human medicine as a last-resort antimicrobial agent to treat infections caused by multidrug-resistant Gram-positive pathogens, such as VRE [ 107 , 108 ]. This drug class is not approved for food animals in the USA and EU and, as expected, Tyson et al (2018) reported very low levels of linezolid-resistant Enterococcus spp.…”
Section: Enterococcus Sppmentioning
confidence: 99%